2010
DOI: 10.1080/00071668.2010.522556
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcase quality in broiler chickens fed on bacterial protein grown on natural gas

Abstract: 1. The effects of increasing concentrations (0, 40, 80 or 120 g/kg) of bacterial protein meal (BPM) and bacterial protein autolysate (BPA) grown on natural gas on growth performance and carcase quality in broiler chickens were examined. 2. Adding BPM to diets reduced feed intake and improved gain: feed from 0 to 21 d and overall to 35 d, but did not significantly affect weight gain compared to the soybean meal based control diet. 3. Increasing concentrations of BPA significantly reduced growth rate, feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
2
8
0
Order By: Relevance
“…Similar to our study, feed intake of broiler chickens decreased with increasing levels of bacterial meal in diets ( Schøyen et al., 2007b , Øverland et al., 2010a ), which was also reported for broiler chickens fed with diets supplemented with low levels (<2%) of vinasse-grown C. jadinii at the expense of SBM ( Chand and Ullah Khan, 2014 ). Both yeast and bacterial meal are rich in nucleic acids when compared with conventional feed ingredients ( Castro et al., 1971 , Mateo et al., 2004 , Mateo and Stein, 2004 , Hellwing et al., 2007 ), which may increase dietary nucleic acid content and reduce feed intake in birds ( Kubota and Karasawa, 1994 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our study, feed intake of broiler chickens decreased with increasing levels of bacterial meal in diets ( Schøyen et al., 2007b , Øverland et al., 2010a ), which was also reported for broiler chickens fed with diets supplemented with low levels (<2%) of vinasse-grown C. jadinii at the expense of SBM ( Chand and Ullah Khan, 2014 ). Both yeast and bacterial meal are rich in nucleic acids when compared with conventional feed ingredients ( Castro et al., 1971 , Mateo et al., 2004 , Mateo and Stein, 2004 , Hellwing et al., 2007 ), which may increase dietary nucleic acid content and reduce feed intake in birds ( Kubota and Karasawa, 1994 ).…”
Section: Discussionsupporting
confidence: 89%
“…They observed similar weight gain in birds fed with the diets supplemented with 39 to 43% CP from yeast, compared with those fed with SBM-based diets, but weight gain was lower in birds fed with diets supplemented with 59 to 65% yeast CP. On the contrary, broiler chickens fed with diets containing bacterial meal comprising 17 to 34% of dietary CP had higher or similar weight gain than birds fed with SBM-based diets ( Schøyen et al., 2007a , Øverland et al., 2010a ). In addition, the same strain of C. jadinii successfully replaced up to 40% of the CP from conventional protein sources in diets for weanling piglets, and the growth performance of the pigs was maintained ( Cruz et al., 2019 ).…”
Section: Discussionmentioning
confidence: 86%
“…The changes in fatty acid composition from adding 8% bacterial autolysate to diets were, however, less pronounced than those reported when adding 8% of bacterial meal, using the same control diet (Øverland et al., 2011). This could be due to a slightly lower lipid content in the bacterial autolysate compared with bacterial meal as reported by Øverland et al. (2010a).…”
Section: Resultsmentioning
confidence: 77%
“…Bacterial meal (BioProtein) produced by fermentation of natural gas by the bacteria Methylococcus capsulatus (>95%), together with Ralstonia sp., Aneurinibacillus sp. and Brevibacillus agri ., has shown to be a high‐quality feed ingredient for broiler chicken (Skrede et al., 2003; Schøyen et al., 2007a; Øverland et al., 2010a). The bacterial meal is a reddish‐brown dry powder containing approximately 96% dry matter, 70% crude protein with a well‐balanced amino acid profile, 10% lipids and 7% ash (Øverland et al., 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, Overland et al [3637] reported improved FCR (p<0.05) due to inclusion of bacterial protein autolysate at 12% replacing soybean meal in broiler diet. In our study, improved FCR was seen at 2.5 and 5% inclusion levels of SCP in the diet.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%